As relações de trabalho e as relações afetivas como veículos de sociabilidade do indivíduo, na obra Alguém para amar a vida inteira, de Roniwalter Jatobá - Monteiro, Ana Lucia Barbosa (2021)
This thesis analyzes work relationships and emotional relationships as channels for the individual’s sociability in the novel “Someone to Love a Whole Life”, by Roniwalter Jatobá, whose literary production has focused on the life of Brazilian workers, demonstrating that the labor world, despite dreadful and arduous, provides love, fraternity, and sociability among workers. The narrative features hardworking characters, whose voices focus on the labor world and emotional relationships, within and outside the work environment. Issues related to the labor universe are prominent in the work of this writer, giving meaning to the characters’ lives. Jatobá has made important insertions in contemporary fiction with an under-explored theme in canonical texts of Brazilian literature: living conditions of Brazilian migrant workers. For Jatobá, human condition should not have an innocuous status in literature, from a social and political point of view. Life and art are in constant dialogical relationships. The research follows the methodological orientation of the Dialogic Discourse Analysis (DDA), present in Mikhail Bakhtin and the Circle, articulating literary discourse and life. As for the problematization of the work universe, it is primarily based on the Marxist reflections of Georg Lukács, Ricardo Antunes, Karl Marx and Friedrich Engels, Richard Sennett, and André Gorz. In the field of literature, the theoretical reflections conducted are based on Alfredo Bosi, Antônio Candido and Bakhtin and the Circle, connecting literature and society. Results obtained indicate that the writer literarily constructs critical discourses about the work universe in the troubled industrial context of the city of São Paulo, in twentieth-century urban Brazil. The narratives portray an identity for Brazilian workers shaped in a scenario of ethical confrontations and struggle for survival, in which social tensions manifest severe relations of submission and authoritarianism in the labor world. In this universe, work relationships and emotional relationships compete. Therefore, the work universe, despite dreadful and arduous, provides love, sociability, and fraternity among workers, enabling the characters’ sentimental education, implying, in certain moments, character redemption, such as the case of the protagonist Jacinto, which although immersed in the bitter labor world, after intense ethical confrontation, was skillfully able to get involved in a pure, simple, and beautiful feeling, like love. This feeling made Jacinto break the bonds and redesign his own life narrative, surrendering to the charms of Emília Emiliano, Someone to Love a Whole Life. Thus, work constitutes a means from which the subject is socially and historically built in daily work, in conflict and in harmony with peers. Both labor activity and discursive reflection on work go hand in hand, demonstrating that the characters not only work, but also ponder on material life. Language and work are interrelated in Jatobá’s literary universe. Literary discourse is no stranger to world events. There is a communicative current between art and life, a lively dialogue, measured by axiological positions.